Several Problems in Particle Physics and Cosmology Solved in One SMASH - Ballesteros, Guillermo; Redondo, Javier; Ringwald, Andreas; Tamarit, Carlos (Frontiers in Astronomy and Space Sciences, 2019)
The Standard Model (SM) of particle physics is a big success. However, it lacks explanations for cosmic inflation, the matter-anti-matter asymmetry of the Universe, dark matter, neutrino oscillations, and the feebleness of CP violation in the strong interactions. The latter may be explained by a complex scalar field charged under a spontaneously broken global U(1) Peccei- Quinn (PQ) symmetry. Moreover, the pseudo Nambu-Goldstone boson of this breaking -the axion- may play the role of the dark matter. Furthermore, the modulus of the PQ field is a candidate for driving inflation. If additionally three extra SM singlet neutrinos (whose mass is induced by the PQ field) are included, the five aforementioned problems can be addressed at once. We review the SM extension dubbed SMASH –for SM-Axion-Seesaw-Higgs portal inflation–, discuss its predictions and tests in astrophysics, cosmology, and laboratory experiments. Variants of SMASH are also considered and commented on.